Optimization of Government Administration Reform: SWOT Analysis of Electronic Land Certificate Implementation through Keyword Visualization Identification - Tambun, Anita Octaria; Nasution, Heranisty; Simanjuntak, Ruth Cahyanti (Borong Newinera Publisher, 2025)
This research explores the implementation of electronic certificates as a strategic step in government administration reform in Indonesia, particularly in the land sector. The implementation of electronic certificates aims to improve administrative efficiency, transparency and security through a digital technology approach in accordance with the principles of good governance. Using the SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis method, this study evaluates the potential and challenges in implementing this policy. The results show that electronic certificates can speed up administrative processes, save operational costs, and increase transparency through digital track records. However, significant challenges such as limited technological infrastructure, resistance to change, and human resource readiness require strategic solutions. With the right policies and planned risk mitigation, electronic certificates have great potential in realizing a more modern, efficient, and inclusive administrative system.